EVALUATION OF NUMBER OF SEEDS PER HOLE ON THE VEGETATIVE GROWTH PERFORMANCE OF MELON (Citrullus colocynthis L.) IN A FOREST SAVANNA TRANSITION ZONE OF EDO STATE - Umeri, Clifford; Ogedegbe, Felix O.; Belonwu, Eunice N.; Nwachukwu, Raymond C.; Aikhu, Joy L. (FUDMA JOURNAL OF SCIENCES, 2025)
This research examined how different numbers of seeds per planting hole affected the vegetative growth of Citrullus colocynthis (Lanatus) at the Teaching and Research Farm, Faculty of Agriculture, Ambrose Alli University, Ekpoma. The site lies in the forest-savanna transition zone of South-South Nigeria (6°08′N, 6°41′E). A randomized complete block design (RCBD) with three replications was used. Prior to planting, soil samples were collected from a 0–15 cm depth and analyzed for their chemical and physical properties. The study involved five treatments with 1 to 5 seeds planted per hole at a spacing of 1 m × 1 m. Vegetative growth indicators—including vine length, number of leaves, leaf area, stem girth, and number of branches per plant—were measured every three weeks. The data were analyzed using ANOVA, and treatment means were compared using the Least Significant Difference (LSD) method. The results showed that at 9 weeks after planting (WAP), plots with three seeds per hole produced the longest vines and the highest number of branches. Meanwhile, the highest number of leaves was recorded in plots with four seeds per hole. The thickest stems (2.89 cm) were observed in plots with either three or four seeds per hole. Additionally, the largest leaf area was found in the three-seed-per-hole treatment. Overall, the findings suggest that planting three seeds per hole results in the most favorable fruiting, which is essential for maximizing melon seed yield in similar agroecological environments.
Keywords: Citrullus colocynthis; Vegetative growth; Melon cultivation; Optimal planting density